Inquiring the inter-relationships amongst grain-filling, grain-yield, and grain-quality of Japonica rice at high latitudes of China - Farooq, Muhammad Shahbaz; Khaskheli, Maqsood Ahmed; Uzair, Muhammad; Xu, Yinlong; Wattoo, Fahad Masood; Rehman, Obaid ur; Amatus, Gyilbag; Fatima, Hira; Khan, Sher Aslam; Fiaz, Sajid; Yousuf, Muhammad; Ramzan Khan, Muhammad; et al. (Frontiers in Genetics, 2022)
Climate change especially has substantially impacted rice production in mid- high-latitudes of China especially Northeast China (NEC). Inquiring the self-adaptability and suggesting adjustive measures to climate variability has practical significance purposing to establish a sustainable rice system. A field study under randomized complete block design (RCBD) was arranged during 2017 and 2018 at Harbin and Qiqihar of Heilongjiang province with four different cultivars viz. Longdao-18, Longdao-21, Longjing-21, and Suijing-18 to inquire the inter-relationships between grain-filling parameters, grain yield and grain quality. Current study evaluated that formation of the filling-material for superior and inferior grains was mainly occupied in the middle of grain-filling phase which accounted for 59.60%. Grain yield differences for Suijing-18, Longjing-21, Longdao-21, and Longdao-18 were 8.02%, 12.78%, 17.19% and 20.53% higher at Harbin than Qiqihar, respectively in 2017, and trend was same in 2018. Maximum productive tillers were observed in Suijing-18 at Harbin with mean values of 17 and 15, respectively, during 2017 and 2018. The grain-filling parameters of yield analysis showed that Harbin-filling duration of growth was conducive to increased yield but the factor in limiting yield at Qiqihar was mainly the low dry-weight of inferior grains. The results of this study showed that the average value of protein contents at Harbin were significantly higher (8.54% and 9.13%) than Qiqihar (8.34% and 9.14%) in 2017 and 2018, respectively. Amylose contents showed significantly elevated values of 20.03% and 22.27% at Harbin than Qiqihar of 14.44% and 14.67% in 2017 and 2018, respectively. Chalkiness percentage was higher at Qiqihar which showed that Harbin produced good quality rice. Given these self-adaptability mechanisms to climatic variability and inter-relationships between grain-filling and grain yield, there is an imperative requirement to investigate and explore more measures to improve Japonica rice sustainability with better adaptation to increasingly climatic variabilities.